Sosialisasi dan Pelatihan Teknologi Hasil Perairan dengan Menerapkan Cara Produksi Pangan Olahan yang Baik di Kampung Babakan Limbangan, Kecamatan Sukaraja, Kabupaten Sukabumi - Ita Srihastuti; Danang Aria Nugroho; Sugeng Heri Suseno (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2019)
The Babakan Limbangan Village was one of village in the Sukaraja, Sukabumi district. This an area develops the aquaculture and fisheries processing sectors. Quality assurance system the products has not been done at the processing location. The processing group in Babakan Limbangan village, Sukabumi need to be given knowledge for food safety, quality assurance systems and apply Good Manufacturing Practics (GMP). The purpose of this activity is increase comunmunity knowledge of food safety and creativity. The infomation transfer was done by seminar and make a products. The results of this activity there was increase the knowledge of the community how to process fishery products with good quality and skill of partners about aquatict product technology.